Acculturation and Campus Carry: Examining the Effect of Mexico Versus United States Cultural Orientations on College Students’ Support for Campus Carry - Updegrove, Alexander H. (International journal of offender therapy and comparative criminology, 2021)
Several U.S. states have authorized carrying concealed firearms on campuses. These measures are controversial, with support falling along ideological lines. This study examines whether cultural proximity to the U.S., relative to Mexico, influences support for campus carry. Using a random sample of 1,447 college students from two Texas public universities, structural equation modeling results revealed that individuals more oriented toward U.S. culture were more likely to support campus carry than individuals oriented more toward Mexican culture. Besides this direct effect, acculturation also indirectly influenced support for campus carry through public attitudes toward the police. Specifically, individuals more oriented toward the U.S. held more favorable views of the police, which in turn predicted greater support for campus carry. Collectively, these findings suggest that cultural values influence support for public policies such as campus carry.